2021
DOI: 10.1002/anie.202100717
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Metallophthalocyanine Framework Films with High Carrier Mobility as Efficient Chemiresistors

Abstract: The poor electrical conductivity of two‐dimensional (2D) crystalline frameworks greatly limits their utilization in optoelectronics and sensor technology. Herein, we describe a conductive metallophthalocyanine‐based NiPc‐CoTAA framework with cobalt(II) tetraaza[14]annulene linkages. The high conjugation across the whole network combined with densely stacked metallophthalocyanine units endows this material with high electrical conductivity, which can be greatly enhanced by doping with iodine. The NiPc‐CoTAA fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 89 publications
1
91
0
Order By: Relevance
“…32–44 Moreover, the associated unique features such as strong CO 2 adsorption capacity and single active sites make COFs to be a good choice for CO 2 RR. 45–57 Since Yaghi and co-workers first reported that the cobalt porphyrin-based COF-366-Co can catalyze the CO 2 RR to produce CO, 58 several other metal porphyrin- and phthalocyanine-based COFs have been reported as electrodes to promote the CO 2 RR in aqueous medium. 59,60 However, due to the face to face lamellar stacking, the active sites in the layers of 2D COFs cannot be fully exposed to electrolytes and CO 2 , which usually leads to low activity and current density.…”
Section: Introductionmentioning
confidence: 99%
“…32–44 Moreover, the associated unique features such as strong CO 2 adsorption capacity and single active sites make COFs to be a good choice for CO 2 RR. 45–57 Since Yaghi and co-workers first reported that the cobalt porphyrin-based COF-366-Co can catalyze the CO 2 RR to produce CO, 58 several other metal porphyrin- and phthalocyanine-based COFs have been reported as electrodes to promote the CO 2 RR in aqueous medium. 59,60 However, due to the face to face lamellar stacking, the active sites in the layers of 2D COFs cannot be fully exposed to electrolytes and CO 2 , which usually leads to low activity and current density.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, no apparent change of current was observed toward 10 commonly cross‐sensitive gases involving SO 2 , [20] a representative interference gas for NO 2 , implying that Co‐TPCOF possessed excellent selectivity. As far as we know, such unusual specific selectivity has rarely been reported for NO 2 sensing materials [3a, 4, 10b] …”
Section: Resultsmentioning
confidence: 96%
“…2,[8][9][10][11][12] In this regard, 2D polymers with columnar assemblies, so called 2D covalent organic frameworks (COFs), have emerged as ideal platforms for constructing photoconductive devices since they fulfil both descript criteria, but have the shortcoming of requiring elaborate structural design and considerable synthetic effort to obtain specific alignment. [13][14][15][16][17][18][19] Moreover, studies also report that such design also increases the photo responsive speed of polymers compared to disordered 2D p-conjugated polymers. 8 However, one should note that, while 2D columnar assembly increases the conductivity of the generated electricity due to additional conductive pathways, at the same time it causes a reduction of electric generation due to limited absorption of photons by adsorbents.…”
Section: Introductionmentioning
confidence: 95%
“…2,8–12 In this regard, 2D polymers with columnar assemblies, so called 2D covalent organic frameworks (COFs), have emerged as ideal platforms for constructing photoconductive devices since they fulfil both descript criteria, but have the shortcoming of requiring elaborate structural design and considerable synthetic effort to obtain specific alignment. 13–19 Moreover, studies also report that such design also increases the photo responsive speed of polymers compared to disordered 2D π-conjugated polymers. 8…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation